2011
DOI: 10.1264/jsme2.me11123
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Acetogenic Population in a Mesophilic Anaerobic Digester in Response to Increasing Ammonia Concentration

Abstract: Changes in the acetogenic population were investigated in an experimental laboratory-scale biogas reactor (37°C) subjected to gradually elevated ammonia levels (0.8 to 6.9 g NH4 + -N L −1 ). A shift from aceticlastic acetate degradation to syntrophic acetate oxidation had previously been confirmed in this reactor. In a parallel control reactor, operating at constant ammonia levels (0.65-0.90 g NH 4 + -N L −1 ), acetate degradation proceeded via the aceticlastic pathway throughout the operating period (660 d). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 34 publications
4
45
1
Order By: Relevance
“…In a previous study, it was found that slight inhibition happened until the ammonia nitrogen concentration was tested to be 3000 mg/L in a piggery waste experiment (50). It was also reported that for dealing with organic municipal wastes, the process remained stable and the methane yield kept normal at the pH value of 7.9 and ammonia nitrogen concentration reached 3300 mg/L (51). Some researchers also suggested that free ammonia which was determined by three parameters (total ammonia concentration, temperature and pH) was the most important component causing ammonia inhibition (21,25) and the advised value of free ammonia was below 150 mg/L (52) or at least no more than 220 mg/L which was the half toxic inhibition constant (53).…”
Section: Resultsmentioning
confidence: 95%
“…In a previous study, it was found that slight inhibition happened until the ammonia nitrogen concentration was tested to be 3000 mg/L in a piggery waste experiment (50). It was also reported that for dealing with organic municipal wastes, the process remained stable and the methane yield kept normal at the pH value of 7.9 and ammonia nitrogen concentration reached 3300 mg/L (51). Some researchers also suggested that free ammonia which was determined by three parameters (total ammonia concentration, temperature and pH) was the most important component causing ammonia inhibition (21,25) and the advised value of free ammonia was below 150 mg/L (52) or at least no more than 220 mg/L which was the half toxic inhibition constant (53).…”
Section: Resultsmentioning
confidence: 95%
“…A recent metaproteome study came to very similar conclusions at the protein level [80]. Also at high ammonia levels, there are many lines of evidence confirming that strictly hydrogenotrophic Archaea with different syntrophic bacterial partners are the workhorse teams producing methane via the acetate oxidation pathway (SAO) at meso-and thermophilic conditions [48,[81][82][83]. The most important reason for these strain-and stressinduced population shifts is probably that particularly Methanobacterium and Methanothermobacter archaea have higher growth rates than Methanosarcina representatives and are thus more capable of coping with the dilution rate under the influence of stress factors in flow-through processes.…”
Section: Microbial Bioindicatorsmentioning
confidence: 85%
“…The program used was as follows: initial temperature of 95°C for 7 min followed by 55 cycles of 95°C for 40 s, 58°C (for total methanogens, 66°C, and for the order Methanobacteriales, 60°C) for 60 s, and 72°C for 40 s. DNA standard curves were prepared from pure cultures of Methanobrevibacter ruminantium DSMZ 1093 and Methanoculleus bourgensis DSMZ 3045 using the specific primer sets for Methanobacteriales, Methanomicrobiales, and total methanogens. The standard was prepared as described in the work of Westerholm et al (40). The specificity of the target PCR product was estimated by melt curve analysis, which consisted of 50 gradual denaturation cycles.…”
Section: Methodsmentioning
confidence: 99%